PENGARUH SELFING TERHADAP KARAKTER TANAMAN JAGUNG ( Zea mays L.) PADA GENERASI F4 SELFING - Yunita Armaya Lubis; Lollie Agustina P.Putri2 Lollie Agustina P.Putri2 Lollie Agustina P.Putri2; Rosmayati Rosmayati (Universitas Sumatera Utara, 2013)
The objective of the research was to evaluate variability’s of several characters affected by the variants genotype (σ2g), variants phenotype (σ2p), and studied heritability and also evaluated the effect selfing of F4 with it’s parents of corn (Zea mays L.). The experiment was conducted at Setia Budi, Kelurahan Simpang Selayang, Kecamatan Medan Tuntungan, Medan. with altitude ± 25 meters above sea level from April 2012 to July 2012, used Randomized Block Design with one factor and four replication. The result of the research is genotype have significant effect to characters the curvature of leaf, the age of harvest, the dry kernel per ear, and the rate of seed filling. From progeny test results between F4 to F3 shows the difference in plant height character in genotype VCD, VEF, the affect time of male flowering character in genotype VAB, VBA, VDC, the affect time of female flowering character in all genotype, the curvature of leaf the character in genotype VBA, VCD, VEF, VFE, the number of leaves above the cob character in genotype VAB, VDC, VFE, the age of harvest character in genotype VAB, VBA, VCD, VDC, VFE, the number of kernel per ear character in genotype VDC, VEF and VFE, the production dry kernel per plot character in genotype all genotype and the rate of seed filling character in genotype VAB, VCD, VDC, VEF and VFE. The genotype variability of all characters showed range pressed variability and phenotype variability characters showed range wide and pressed variability, heritability showed range low,medium and high heritability. Key word : corn, selfing, heritability, variability